Profil Multiple Intelligences Mahasiswa Perikanan dalam Pembelajaran - Sambeka, Yana; Kuendo, Wilce Anna Cahya; Haryanti Putri Rizal (Innovative: Journal Of Social Science Research, 2024)
Multiple intelligences are very important, as they help individuals develop the diverse abilities needed to adapt and thrive. Each individual has a different type of intelligence. Each individual with different types of intelligence can influence the way they learn. This research aimed to identify students' multiple intelligences profile in learning as part of a preliminary study. The research method applied was a quantitative method, with the total number of respondents being 19 students. The instrument used was a questionnaire/questionnaire using a Likert scale. The interpretation of calculation scores, assessment intervals, and calculation of the index formula (%) were carried out. The results showed that interpersonal intelligence is the most dominant type of intelligence (79,74%) and musical intelligence is the lowest (55,13%). Based on the results of the research, it can be concluded that the majority of multiple intelligences types are in the high category, except musical intelligence in the low category.